1974
DOI: 10.1021/ic50132a024
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-transform carbon-13 nuclear magnetic resonance study of (arene)tricarbonylchromium complexes

Abstract: 13C nmr spectroscopy was employed to study the perturbations in bonding for monosubstituted benzene derivatives upon complexation with Cr(CO)3. An analysis of the C(4) 13C nmr chemical shifts of both free and complexed arenes implies that there is no significant change in the transmission of resonance substituent effects upon complexation. A similar analysis of the C(l) 13C nmr chemical shifts and the ' 3 * coupling constants indicates a net withdrawal of electron density by the Cr(CO)3 fragment from the a fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…This remarkable constancy of the dominance of the resonance parameter in the transmission of substituent effects is most gratifying especially as a recent 13C n.m.r. study showed exactly comparable behavior (18). The correlation between the lgF chemical shifts in para-substituted fluorobenzenes and the 13C chemical shift of the C, carbon in the corresponding monosubstituted arenes is well established (25), and this relationship still holds in most cases when the arenes are complexed (see Fig.…”
Section: Methodsmentioning
confidence: 54%
“…This remarkable constancy of the dominance of the resonance parameter in the transmission of substituent effects is most gratifying especially as a recent 13C n.m.r. study showed exactly comparable behavior (18). The correlation between the lgF chemical shifts in para-substituted fluorobenzenes and the 13C chemical shift of the C, carbon in the corresponding monosubstituted arenes is well established (25), and this relationship still holds in most cases when the arenes are complexed (see Fig.…”
Section: Methodsmentioning
confidence: 54%
“…'J(RhP) is usually considered to reflect the strength of the u component of the b~nding.,~-~" The general trend for lJ(RhP) is an increase with the basicity of the p h~s p h i n e .~~ Nevertheless, the reverse behaviour, a decrease in ' J ( M P ) with increasing basicity of the phosphine ligand, has already been observed where M = Rh4', M = Pt.41 compounds [Rh.Cl.cod.PRJ (30)(31)(32)(33).…”
Section: Influence Of Back-bondingmentioning
confidence: 99%
“…Coordination of an arene to a transition metal causes large shifts to lower frequencies of the ring C-resonances in respect to the free arene [15]. The increase in shielding has been variously attributed to metal ligand bond anisotropy [ 16-181, changes in ring C-hybridization [19] and changes in electron density in the 0- [20] [21] and n- [22- interpretation of these shifts is not yet available [26] [27], however, a thorough study of the factors that influence the coordination shift concludes that changes in n-electron density and, particularly, metal to arene n*-backbonding play a dominant role in the observed shielding of coordinated arenes [23]. These conclusions receive support from the results of molecular orbital calculations [25] [28-301 and a He (I) photoelectron study [3 11.…”
mentioning
confidence: 99%